Evaluación del mucílago de cacao (theobroma cacao l) para la obtención de etanol de segunda generación - Jordan Cobos, Karen Pamela; Parra Flores, Maria Del Cisne (Machala : Universidad Técnica de Machala, 2020)
This research was carried out in order to evaluate the cocoa mucilage (Theobroma Cacao L) for the production of second generation ethanol through the alcoholic fermentation process, with which it is intended to take advantage of this by-product that is generated in the harvest of the beans of cocoa, since it has fermentative properties. To start the fermentation process, the cocoa mucilage was first collected under aseptic conditions, the physicochemical characteristics of the sample were determined by the respective analyzes such as: pH (potentiometry), ° Brix (refractometry), titratable acidity (acid-base titration), humidity (thermo gravimetric), ash (calcination) and reducing sugar content (3,5-dinitrosalicylic acid). The fermentation process begins when the reducing sugars present in the mucilage are transformed into ethanol and there is the formation of carbon dioxide (CO2), where the pH increased and the fermentation temperature was constant. In this investigation, 4 treatments were carried out, in which two types of fermentation, spontaneous and controlled, were established. To carry out spontaneous fermentation, the cocoa mucilage was placed in an incubator with constant stirring at a temperature of 25 ° C. In the controlled fermentation, the sample was autoclaved first at a temperature of 121 ° C for 15 minutes, in order to eliminate microorganisms that could affect the fermentation process. It was allowed to cool for an hour until reaching a temperature of 30 ° C, to proceed with the inoculation, commercial Saccharomyces cerevisiae yeast (1 g / L) was used, it was fermented under the same conditions as the spontaneous fermentation treatment , using an incubator. The controlled fermentation treatments performed were; pH adjustment, nutrient addition (NH4) 2SO4 and yeast. The fermentation process was 7 days, in which a pH control, quantity of reducing sugars and ethanol concentration were carried out, taking sample every 24 hours.
Esta investigación se realizó con la finalidad de evaluar el mucílago de cacao (Theobroma Cacao L) para la producción de etanol de segunda generación mediante el proceso de fermentación alcohólica, con la cual se pretende aprovechar este subproducto que se genera en la cosecha de los granos de cacao, ya que este posee propiedades fermentativas. Para iniciar el proceso de fermentación, se llevó a cabo primero la recolección del mucílago de cacao en condiciones asépticas, se determinó las características fisicoquímicas de la muestra mediante los análisis respectivos tales como: pH (potenciometría), °Brix (refractometría), acidez titulable (valoración ácido-base), humedad (termo gravimétrico), cenizas (calcinación) y contenido de azúcares reductores (ácido 3,5-dinitrosalicílico). El proceso fermentativo se inicia cuando los azúcares reductores presentes en el mucílago se transforman en etanol y existe la formación de dióxido de carbono (CO2), en donde el pH aumentó y la temperatura de fermentación fue constante. En esta investigación se realizó 4 tratamientos, en los cuales se estableció dos tipos de fermentación, espontánea y controlada. Para llevar a cabo la fermentación espontánea, el mucílago de cacao se lo puso en una incubadora con agitación constante a temperatura de 25 °C. En la fermentación controlada primero se esterilizó en autoclave la muestra a temperatura de 121 °C durante 15 minutos, con la finalidad de eliminar microorganismos que puedan afectar el proceso de fermentación. Se dejó enfriar durante una hora hasta llegar a una temperatura de 30 °C, para proceder a realizar la inoculación se utilizó levadura Saccharomyces cerevisiae comercial (1 g/L), se procedió a fermentar en las mismas condiciones que el tratamiento de la fermentación espontánea, utilizando una incubadora. Los tratamientos de fermentación controlada realizados fueron; ajuste de pH, adición de nutriente (NH4)2SO4 y levadura. El proceso fermentativo fue de 7 días, en los cuales se llevó un control de pH, cantidad de azúcares reductores y concentración de etanol, tomando muestra cada 24 horas.
Keywords: THEOBROMA CACAO L, MUCILAGO; SACCHAROMYCES CEREVISIAE; GLUCOLISIS; FERMENTACION